PERSEPSI GURU GEOGRAFI PADA METODE PEMBELAJARAN PROBLEM BASED LEARNING DI SMA NEGERI 13 PANGKEP MENURUT SINTAK KURIKULUM 2013 - Khaerunnisa Khaerunnisa; Ibrahim Abbas; Erman Syarif (UNM Geographic Journal, 2021)
This study aims to determine how the application of geography teachers in using the Problem Based Learning model. Data was collected through interviews with teachers in the field of geography. Using qualitative analysis conducted by means of interviews and observations. The results showed that geography teachers at SMA Negeri 13 Pangkep in Labakkang District, Pangkep Regency, the teachers had implemented a problem-based learning model based on the 2013 curriculum following training workshops and already knew the syntax and steps of learning geography by applying the PBL learning model. This shows that the teaching skills of geography teachers at SMA Negeri 13 Pangkep under study are quite good. Teachers also began to use information and communication technology in the teaching and learning process in the classroom.